HARDNESS WATER REMOVAL BY USING CELLULOSE PAPYRUS FIBERS (Borrasus flabelifer L) FROM EAST NUSA TENGGARA MODIFIED WITH CITRIC ACID - Solo, Anna Apriani Maniuk; Rumhayati, Barlah; Masruri, (Media Konservasi, 2023)
Hardness water removal using adsorbent ester cellulose citrate from Papyrus Fibers (Borrasus flabelifer L) from East Nusa Tenggara modified with citric acid has been done. The Adsorbent was modified with 0.6 mol/L citric acid at 120o C for one-half hour. The Adsorbent ester cellulose citrate from papyrus fibers (Borassus flabelifer L) has an ester carbonyl functional group (C=O) and O-H alcohol active group (O-H), which react to Ca2+ and Mg2+ from hardness water. The effects of adsorption conditions, such as contact time, pH, and hardness water concentrations were studied. The result shows that ester cellulose citrate from Papyrus Fibers (Borrasus flabelifer L) can remove hard water. The best condition for adsorption hardness water using ester cellulose citrate adsorbent from papyrus fibers in 6 h contact time with pH 6 and 250 mg/L as CaCO3 hardness water. The hardness of water removal is up to 71%.   Key words: adsorbent; agricultural waste; citric modified; estererification; hardness water